Linking sustainability to competitiveness - Muolo, Alessandro; Salvati, Luca (Routledge, 2026)
This book identifies and discusses opportunities and constraints in applying the sustainability paradigm to urbanization. It integrates this wide concept with 'local competitiveness' and focuses on the role of both general and specific political action in shaping the economic structure of a region.By linking sustainability and local competitiveness within metropolitan regions, it offers an innovative exploration of urbanization processes. Moving beyond the usual institutional and regional economic approaches, the book integrates perspectives from economic geography, sociology, demography, ecology, and planning. It presents practical tools and real-world data, enabling readers to interpret and delve into new urban development paths. By exploring the interaction between urban sustainability and economic competitiveness, a framework is provided that supports informed policymaking decisions at local, regional, and national scales.This book is written for academics and students-from undergraduates to doctoral candidates-who want a clear, practical look at how local economies, sustainability, and competitiveness come together. It is also helpful for professionals, policymakers, and for anyone curious about how economic growth might become a long-term sustainable political goal.